Análise da aprendizagem de leitura e escrita em indivíduos com Síndrome de Williams - Fava, Letícia Regina (2023)
Williams Syndrome (WS) is a genetic condition resulting from the deletion of approximately 20 genes in the 7q11.23 region. The literature reports significant challenges in learning and delays in the acquisition of reading in individuals with this syndrome. Researchers have shown interest in the learning and memory processes involving this group, especially concerning expressive and receptive language, as well as other cognitive aspects. One of the frequently mentioned difficulties relates to learning to read and write. This justifies the present research, whose objective was to explore the acquisition of reading and writing and to program teaching conditions consistent with the learning profiles of four participants diagnosed with WS. To achieve this goal, the computerized teaching program Learning to Read and Write in Small Steps (ALEPP) was used, complemented by activities and procedures tailored to the specific needs of each student. Data related to the progress in reading acquisition of the participants were analyzed. Initially, they were subjected to reading and writing assessments (ARLE Scale), auditory comprehension (Peabody Picture Vocabulary Test - PPVT and USP Picture Vocabulary Test - TVfusp), cognition (WISC-III - Wechsler Intelligence Scale for Children – Third Edition or WAIS-III - Wechsler Adult Intelligence Scale – Third Edition), and academic performance (School Performance Test - TDE). The work was organized into studies, aiming to determine if the students achieved the proposed learning objectives for different levels of competence. In Study 1, which aimed to evaluate the performance of two participants in prerequisite tasks for reading acquisition, the results indicated accuracy in copy tasks with constructed response and also in handwritten copy. These findings strengthen the conclusion that the textual stimulus began to exert control not only over the response modality used during teaching but also over the response of handwriting. Additionally, one of the participants was enrolled in ALEPP Module 1. In Study 2, P1 and P2 learned to read nine simple words through the stimulus pairing with orientation response procedure (PERO). In Study 3, during the teaching phase, three participants (P2, P3, and P4) were exposed to Module 1 (with 17 stages of teaching simple words) and two to Module 2 (with 80 stages of teaching words with orthographic irregularities) of ALEPP. P3 and P4 completed Module 1 and performed the first three Units of Module 2. For each participant, it was necessary to implement a teaching procedure with specific sequence and tasks, aiming to ensure they achieved a performance with 100% accuracy in reading tasks. The results of this study are in line with the literature, which highlights the significant delay and heterogeneity in reading levels of this population, emphasizing the need to improve effective teaching strategies for the development of reading skills in individuals with WS. Overall, the studies showed remarkable progress of the participants, under teaching contingencies previously evaluated as effective with other populations.